Assessing the threat of Bacillus cereus: From toxin characterization to modern detection strategies - Ruibing Tian; Shuang Sun (Food Chemistry, 2026)

pH-switchable polyoxometalate-loaded hydrogel with intrinsic oxygen-independent singlet oxygen generation and in situ nitric oxide production for infected wound management - Cantong Sun; Zhen Zhang; Zhen Li; Muhammad Adnan Younis; Hongyu Chen; Shujun Zhang; Junle Wu; Dehao Du; Haiyan Ge; Lehao Liu; Ruiheng Li; Shengyi Dongye; et al. (Chemical Engineering Journal, 2026)

Screening nutrient sources to enhance biomass and eicosapentaenoic acid (EPA) production in the diatom Chaetoceros lorenzianus - Yijia Zhang; Ruibing Peng; Jiongming Zhang; Maowang Jiang; Xiamin Jiang; Jiayi Sun; Guoquan Zeng (Journal of Applied Phycology, 2026)

Pan-cancer Distant Metastasis Prediction Based on Graph Neural Network - Fengyun Zhang; Qiangguo Jin; Changming Sun; Ruibing Chen; Jie Geng; Siqi Chen; Wenrun Cai; Xugang Sun; Xiaofeng Liu; Ran Su (Interdisciplinary Sciences: Computational Life Sciences, 2026)

DPE1, a novel allelic of BT1, is critical for maize endosperm development and carbohydrate metabolism - Shuai Wang; Yuandong Wang; Ruyang Zhang; Qian Liu; Tianyi Wang; Zhiyong Li; Xiaqing Wang; Chunhui Li; Senlin Xiao; Yanyan Jiao; Jinfeng Xing; Xuan Sun; et al. (Plant Science, 2025)

Evaluation of different microalgal diets on feeding efficiency, growth performance, proximate composition, fatty acid composition, and digestive enzyme activities in juvenile Manila clam (Ruditapes philippinarum) - Jiayi Sun; Xu Chen; Yushun Lu; Jiahuan Wang; Jiongming Zhang; Guoquan Zeng; Xiamin Jiang; Ruibing Peng (Aquaculture International, 2025)

Ultrasmall polylysine dendrimer nanodots for glutathione-responsive targeted chemotherapy and enhanced photodynamic/immunotherapy of metastatic cancer - Ruibing An; Qianting Zhang; Dehao Du; Cantong Sun; Shujun Zhang; Junle Wu; Muhammad Adnan Younis; Haiyan Ge; Kaiqi Wang; Muhammad Rizwan Younis; Jian Dong (Chemical Engineering Journal, 2025)

Fluvoxamine, an inhibitor of CYP1A2, improves CS-induced pulmonary inflammation through estrogen deficiency - Siyu-Yang; Ruibing-Sun; Liqing-Wang; Mingzhe-Cao (Toxicology and Applied Pharmacology, 2025)

JEV NS1' protein enhances cell-to-cell viral spread by inducing the formation of tunneling nanotubes - Ziyu Cao; Shengda Xie; Xingmiao Yang; Ning Wei; Yundi Zhao; Mengyuan Sun; Xinxin Lin; Miaolei Shi; Ruibing Cao (Veterinary Microbiology, 2025)

Intracellular MRSA-targeted lipid-polymer hybrid nanoparticles for macrophage reprogramming and intracellular MRSA eradication - Yue Cai; Meilin Qiao; Xiuzhi Xie; Yujie Zhou; Ruibing Yu; Fuhang Song; Hong Wang; Huawei Zhang; Xuanrong Sun (Chemical Engineering Journal, 2025)

Bacterial and fungal communities exhibit contrasting patterns in response to marsh erosion: A fine-scale observation - Minjie Hu; Dongyao Sun; Jordi Sardans; Ruibing Yan; Hui Wu; Ranxu Ni; Josep Peñuelas (CATENA, 2024)

Microbial diversity and keystone species drive soil nutrient cycling and multifunctionality following mangrove restoration - Minjie Hu; Jordi Sardans; Dongyao Sun; Ruibing Yan; Hui Wu; Ranxu Ni; Josep Peñuelas (Environmental Research, 2024)

Dual fluorophores embedded in zeolitic imidazolate framework‑8 for ratiometric fluorescence sensing of a biomarker of anthrax spores - Xiaoran Zhang; Qi Wang; Xincheng Sun; Muhammad Asif; Ayesha Aziz; Yuan Zhang; Chuan Dong; Ruibing Wang; Shaomin Shuang (Chemical Engineering Journal, 2024)

Establishment and clinical application evaluations of a deep mining strategy of plasma proteomics based on nanomaterial protein coronas - Jianan Wang; Wei Xie; Longqin Sun; Jingli Li; Songfeng Wu; Ruibing Li; Yan Zhao (Analytica Chimica Acta, 2023)

Polyvinyl alcohol/montmorillonite/magnesium diboride fibers with superior flame retardancy, strength, and flexibility - Wei Wang; Juan He; Chunlin Li; Nan Zhang; Xuexia He; Qi Li; Jie Sun; Ruibing Jiang; Zhibin Lei; Zong-Huai Liu (Chemical Engineering Journal, 2023)

Moderate salinity improves the availability of soil P by regulating P‐cycling microbial communities in coastal wetlands - Minjie Hu; Yixun Le; Jordi Sardans; Ruibing Yan; Yi Zhong; Dongyao Sun; Chuan Tong; Josep Peñuelas (Global Change Biology, 2023)
Accelerated sea‐level rise is expected to cause the salinization of freshwater wetlands, but the responses to salinity of the availability of soil phosphorus (P) and of microbial genes involved in the cycling of P remain unexplored. We conducted a field experiment to investigate the effects of salinity on P cycling by soil microbial communities and their regulatory roles on P availability in coastal freshwater and brackish wetlands. Salinity was positively correlated with P availability, with higher concentrations of labile P but lower concentrations of moderately labile P in the brackish wetland. The diversity and richness of microbial communities involved in P cycling were higher in the brackish wetland than the freshwater wetland. Salinity substantially altered the composition of the P‐cycling microbial community, in which those of the brackish wetland were separated from those of the freshwater wetland. Metagenomic sequence analysis indicated that functional genes involved in the solubilization of inorganic P and the subsequent transport and regulation of P were more abundant in coastal soils. The relative abundances of most of the target genes differed between the wetlands, with higher abundances of P‐solubilization ( gcd and ppa ) and ‐mineralization ( phoD , phy , and ugpQ ) genes and lower abundances of P‐transport genes ( pstB , ugpA , ugpB , ugpE , and pit ) in the brackish wetland. A significant positive correlation between the concentration of labile P and the abundances of the target genes suggested that salinity may, at least in part, improve P availability by regulating the P‐cycling microbial community. Our results suggest that the P‐cycling microbial community abundance and P availability respond positively to moderate increases in salinity by promoting the microbial solubilization and mineralization of soil P. Changes in microbial communities and microbially mediated P cycling may represent microbial strategies to adapt to moderate salinity levels, which in turn control soil function and nutrient balance.

Molecular mechanisms of coronary microvascular endothelial dysfunction in diabetes mellitus: focus on mitochondrial quality surveillance - Danan Sun; Jin Wang; Sam Toan; David Muid; Ruibing Li; Xing Chang; Hao Zhou (Angiogenesis, 2022)

Trace Element Concentrations in Human Tissues of Death Cases Associated With Secondary Infection and MOF After Severe Trauma - Guangtao Xu; Ruibing Su; Bo Li; Junyao Lv; Weiqi Sun; Bo Hu; Xianxian Li; Jiang Gu; Xiaojun Yu (Biological Trace Element Research, 2015)